Concise asymmetric synthesis of two natural oxacyclododecindione-type macrolactones from industrial waste. Issue 29 (30th April 2020) - Liu, Xian; Nie, Huifang; Yao, Lin; Jiang, Ru; Chen, Weiping
Abstract : Asymmetric synthesis of natural oxacyclododecindione-type macrolactones 2 and 3 has been realized for the first time using industrial waste ( S )-1 as starting material. Abstract : ( S )-5-Methyl-tetrahydropyran-2-one 1 is a by-product in the production of key intermediates of steroidal hormones. Asymmetric synthesis of natural oxacyclododecindione-type macrolactones 2 and 3 has been realized for the first time from ( S )-1 in seven and eight steps with 37% and 27% overall yield, respectively.